Patient Satisfaction in a Tertiary Care Government Hospital - Mohammad Zahid; Rabeea Sadaf; Tariq Zubair; Ghazala Shams; Shahnaz Perveen; Faiza Rahman (Gandhara University, 2022)
OBJECTIVES: To determine patient satisfaction in terms of various services such as ease of getting care, in-patient admission, waiting for check-up, staff interaction, medical care, cost of care, and cleanliness in a Tertiary Care Government Hospital. METHODOLOGY: The study design was cross sectional observational. A total of 200 patients meeting our inclusion criteria were enrolled through convenient sampling techniques in this research study. A well-designed questionnaire was used for data collection of admitted patients.  RESULTS: Out of 200 patients, 96 (48%) male and 104 (47%) female patients were interviewed. 72% were satisfied with clinical care services, 14% had mixed views while 14% patients were not satisfied at all. CONCLUSION: Patients in general showed their satisfaction in some of the aspects, however, keeping in view the burden a public sector hospital absorbs on a daily basis, and it was imperative to receive unsatisfactory feedback from patients in most of the aspects. Thus, the results of my study recommend to the health care leaders to take practical steps to bring further improvement by developing a proper mechanism for the uplift of public sector hospitals.